Intelligence, personality, and gains from cooperation in pepeated interactions - Proto, Eugenio; Rustichini, Aldo; Sofianos, Andis (Journal of political economy, 2019)
We study how intelligence and personality affect the outcomes of groups, focusing on repeated interactions that provide the opportunity for profitable cooperation. Our experimental method creates two groups of subjects who have different levels of certain traits, such as higher or lower levels of Intelligence, Conscientiousness, and Agreeableness, but who are very similar otherwise. Intelligence has a large and positive long-run effect on cooperative behavior. The effect is strong when at the equilibrium of the repeated game there is a trade-off between short-run gains and long-run losses. Conscientiousness and Agreeableness have a natural, significant but transitory effect on cooperation rates.